2011
DOI: 10.1117/1.3578461
|View full text |Cite
|
Sign up to set email alerts
|

Extended scan depth optical coherence tomography for evaluating ocular surface shape

Abstract: Abstract. Spectral domain optical coherence tomography (SD-OCT) with extended scan depth makes it possible for quantitative measurement of the entire ocular surface shape. We proposed a novel method for ocular surface shape measurement using a custom-built anterior segment SD-OCT, which will serve on the contact lens fitting. A crosshair alignment system was applied to reduce the misalignment and tilting of the eye. An algorithm was developed to automatically segment the ocular surface. We also described the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 40 publications
0
48
0
Order By: Relevance
“…As described, X-Y cross aiming was used with all three devices for fine adjustment of the pupil center. 22 Images were acquired when both aiming windows showed specular reflex on the corneal apex, which indicated that the incident OCT beam was perpendicular to the apex. All the images were acquired by the three OCT devices within half an hour.…”
Section: Methodsmentioning
confidence: 99%
“…As described, X-Y cross aiming was used with all three devices for fine adjustment of the pupil center. 22 Images were acquired when both aiming windows showed specular reflex on the corneal apex, which indicated that the incident OCT beam was perpendicular to the apex. All the images were acquired by the three OCT devices within half an hour.…”
Section: Methodsmentioning
confidence: 99%
“…The first demonstration of anterior segment OCT imaging was performed in 1994 by Izatt et al [63]. Multiple studies demonstrated time-domain OCT and Fourier-domain OCT for anterior segment imaging at different wavelengths and speeds [11,22,[64][65][66][67][68]. Challenges encountered in SD-OCT could be addressed by reducing parasitic sensitivity roll-off and improving light penetration into tissue [69,70].…”
Section: High-speed Anterior Segment Imaging With Ss-octmentioning
confidence: 97%
“…Briefly, the first step was to automatically seg- [36,37]. In this step, the initial anterior corneal boundary was primarily estimated by thresholding and binary morphology [30]. Then, a shortest path search using dynamic programming was applied to optimize the boundary position.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…As described previously [29][30][31][32][33][34][35], the long scan depth SD-OCT system has a superluminescent diode light source (Superlumdiodes Ltd., Moscow, Russia) with a wavelength centered at 840 nm. The axial resolution was ∼7.5 μm in the cornea tissue.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
See 1 more Smart Citation